The Influence of Leadership Style with the Traits Approach Against Student Learning Outcomes - 'Ilma, Zaida Fithrotul; Hariyati, Nunuk (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2024)
In the world of education, the person who plays the most role in leading the running of a school is the principal. A school principal must have abilities that arise from within him because this greatly influences an organization and how he leads all its members. Therefore, the aim of this research is to look at the influence of the principal's leadership style in improving student learning outcomes based on the trait approach. The method used in this literature review is through literature study from various sources, starting from research articles or books. The results shown are the influence of leadership style using a trait approach on student learning outcomes. The better the school principal's leadership style is supported by a trait approach, the more quality leadership patterns will be formed so that it can increase students' enthusiasm for learning so that the learning outcomes obtained will also increase according to learning competency objectives.